Respostas lipidêmicas de coelhos à ingestão de ração suplementada com quefir - Bissoli, Marcos Coelho (2005)
The purpose of the present study was to evaluate the lipidemic responses of rabbits to the intake of different rations formulated with kefir Therefore 40 animals were separated into randomized blocks whose variation sources were sex and treatment Four personally reconstituted pelletized industrial rations were administered (1) control (2) lyophilized kefir (3) kefir suspension and (4) in natura kefir After weaning and adaptation to the ration the animals were submitted to 30 days of experiment when they ingested the different rations Growth was assessed taking into account the initial and final weight and ration consumption Blood samples were taken before the beginning of the experiment and on the 15th and 30th days of ration administration HDL VLDL total cholesterol LDL and triglycerides were analyzed The Castelli II index was calculated by dividing LDL by HDL The statistical analyzes of the growth index was made by the nonparametric test of Mann-Whitney The lipidemic values were contrasted by analyses of the inclination of linear regression curves (slope tests) The results indicate that only the rabbits who received in natura kefir had significantly lesser growth than the others (p<0,05) Only fraction of total cholesterol and HDL had significant increase (p<0,05) and it ocurred only in the in natura kefir animals The Castelli II index indicated that only HDL increase should be considered It was concluded that kefir administration may not be advantageous from the viewpoint of animal production as revealed by the analysis of the results of growth indexes For human health this probiotic can be useful for weight control therapies and prophylactic actions against dyslipidemies However further studies should be stimulated in order to better explain possible risks of kefir continuous consumption